2015
DOI: 10.3109/00207454.2015.1052429
|View full text |Cite
|
Sign up to set email alerts
|

Association of C7673T polymorphism in apolipoprotein B gene with ischemic stroke in the Chinese population: a meta-analysis

Abstract: Our meta-analysis revealed that C7673T polymorphism in apoB gene was significantly associated with increased IS risk in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Studies in a larger population based on a single minority are needed for a more clear observation. For the subgroups of HT, CHD, CI and cholelithiasis in the XbaI analysis, our finding were partially in accordance with the published four articles [ 5 , 9 , 49 - 50 ]. In addition, hyperlipidemia was diagnosed when one of the following four lipids (TC、LDL、HDL and TG ) was more than the normal serum level, and thus the statistical power of the single lipid (such as LDL) to detect differences may be limited due to the smaller involved sample size.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in a larger population based on a single minority are needed for a more clear observation. For the subgroups of HT, CHD, CI and cholelithiasis in the XbaI analysis, our finding were partially in accordance with the published four articles [ 5 , 9 , 49 - 50 ]. In addition, hyperlipidemia was diagnosed when one of the following four lipids (TC、LDL、HDL and TG ) was more than the normal serum level, and thus the statistical power of the single lipid (such as LDL) to detect differences may be limited due to the smaller involved sample size.…”
Section: Discussionsupporting
confidence: 91%
“…To date, accumulated meta-analysis has been performed to clarify the association of genetic polymorphisms with IS risk. Variants in several genes were identified as risk factors for IS, including apolipoprotein B , beta-2 adrenergic receptor , methylenetetrahydrofolate reductase ( MTHFR), and HDAC9 [4953]. However, some other variants, such as IL-6 G572C, PON1 L55M, and CYP11B2 C-344T were not associated with susceptibility to IS [44,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Then, a fixed-effects trans-ethnic meta-analysis was done including all samples (67,162 [49]. The results of any stroke, as well as the subtypes of stroke, were reported in distinct files which consist of any stroke (AS) cases (67,162), any ischemic stroke (AIS) cases (60,341), and large artery stroke (LAS) cases (6,688), cardioembolic stroke (CES) cases (9,006), and small vessel stroke (SVS) cases (11,710). The datasets were downloaded on 14 April 2022.…”
Section: Stroke Gwas Summary Statistics Datamentioning
confidence: 99%
“…The biomarkers for stroke risk assessment of individuals are currently unavailable, warranting the identification of potential biomarkers for stroke risk, which may enhance the stroke risk assessment and develop novel therapeutics. Past genome-wide association studies (GWAS) have identified several risk loci associated with stroke, including rs2304556 (located in FMNL2) and rs1986743 (located in ARL6IP6) [5][6][7][8][9][10]. The latest GWAS meta-analysis of stroke has revealed 89 risk loci associated with stroke [11].…”
Section: Introductionmentioning
confidence: 99%